Vocabulary and the four skills pedagogy, practice, and implications for teaching vocabulary - Clenton, Jon; Booth, Paul (Routledge, 2020)
"This edited volume provides a single coherent overview of vocabulary teaching and learning in relation to each of the four skills (reading, writing, listening, speaking). Each of the four sections presents a skill area with two chapters presented by two leading experts in the field, relating recent advances in the field to the extent that each skill area relates differently to vocabulary and how this informs pedagogy and policy. The book opens with a summary of recent advances in the field of vocabulary, and closes by drawing conclusions from the skill areas covered. The chapters respond to emerging vocabulary research trends that indicate that lexical acquisition needs to be treated differently according to the skill area. The editors have chosen chapters to respond to recent research advances and to highlight practical and pedagogical application in a single coherent volume"--
Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Vocabulary / Study and teaching; Language and languages / Study and teaching; Second language acquisition / Study and teaching